(untitled) (Bangladesh Journal of Anatomy, 2019)
Context : A reliable and valid measurement of hand anthropometry is important for designing dimensionally compatible hand tools, gloves and hand-held devices. Hand grip strength is accepted as an objective index for the functional integrity of upper extremity. The estimation of hand grip strength is of immense importance in determining the efficacy of different treatment strategies, treatment outcome and hand rehabilitation. The present study was planned to determine the various dimensions of hands, average hand grip strength of adult Bangladeshi female garment workers and the relationship between hand grip strength and different anthropometric measurements of hand. Material and Methods: Two hundred female garment workers of 20-25 years of age were selected by purposive non-random sampling from five different garment factories of Dhaka and Narayangonj city. Different dimensions of both hands were measured directly with the help of digital slide caliper and flexible wire. Hand grip strength of both hands was measured by Smedley’s Hand Grip Strength Dynamometer. Result : Body height, weight, BMI, hand length and hand breadth of adult Bangladeshi garmentsworkers showed positive correlation with hand grip strength, but only significant positive correlation was found between hand length and grip strength of right hand (r=+0.197, P<0.05) and left hand (r=+0.405, P<0.001). Bangladesh Journal of Anatomy July 2019, Vol. 17, No. 2, pp. 50-56